Ethionine Suppresses Mitochondria Autophagy and Induces Apoptosis via Activation of Reactive Oxygen Species in Neural Tube Defects - Zhang, Li; Dong, Yanting; Wang, Wenzhuo; Zhao, Taoran; Huang, Tingjuan; Khan, Ajab; Wang, Lei; Liu, Zhizhen; Xie, Jun; Niu, Bo (Frontiers in Neurology, 2020)
Abnormal development of central nervous system (CNS) caused by neural tube defects (NTDs) is not only remained the major contributor in the prevalence of stillbirths and neonatal deaths, but also represents a significant cause of lifelong physical disability in the surviving infants. Ethionine is a non-proteinogenic amino acid and antagonist of methionine. Methionine cycle is essential for the elimination of reactive oxygen species (ROS), while lysosomes are involved in the initiation of autophagy. However, its role in ethionine-induced cell death in neural tube defects, still need to be explored. In this study, we investigated the effect of ethionine on NTDs as well as the underlying mechanism involved in this process. Following the establishment of NTDs model using ethionine-induced C57BL/6 mice, ethionine was intraperitoneally injected at a dose of 500 mg/kg in E7.5. Our study revealed that ethionine has induced mitochondrial apoptosis in NTDs by reducing mitochondrial autophagy both in vivo and in vitro. These results provided a possible molecular mechanism for redox regulation of autophagic process.